Advanced Oxidative Protein Products Cause Pain Hypersensitivity in Rats by Inducing Dorsal Root Ganglion Neurons Apoptosis via NADPH Oxidase 4/c-Jun N-terminal Kinase Pathways - Ding, Ruoting; Sun, Baihui; Liu, Zhongyuan; Yao, Xinqiang; Wang, Haiming; Shen, Xing; Jiang, Hui; Chen, Jianting (Frontiers in Molecular Neuroscience, 2017)
Pain hypersensitivity is the most common category of chronic pain and is difficult to cure. Oxidative stress and certain cells apoptosis, such as dorsal root ganglion (DRG) neurons, play an essential role in the induction and development of pain hypersensitivity. The focus of this study is at a more specific molecular level. We investigated the role of advanced oxidative protein products (AOPPs) in inducing hypersensitivity and the cellular mechanism underlying the proapoptotic effect of AOPPs. Normal rats were injected by AOPPs-Rat serum albumin (AOPPs-RSA) to cause pain hypersensitivity. Primary cultured DRG neurons were treated with increasing concentrations of AOPPs–RSA or for increasing time durations. The MTT, flow cytometry and western blot analyses were performed in the DRG neurons. A loss of mitochondrial membrane potential (MMP) and an increase in intracellular reactive oxygen species (ROS) were observed. We found that AOPPs triggered DRG neurons apoptosis and MMP loss. After AOPPs treatment, intracellular ROS generation increased in a time- and dose-dependent manner, whereas, N-acetyl-L-cysteine (NAC), a specific ROS scavenger could inhibit the ROS generation. Proapoptotic proteins, such as Bax, caspase 9/caspase 3, and PARP-1 were activated, whereas anti-apoptotic Bcl-2 protein was down-regulated. AOPPs also increased Nox4 and JNK expression. Taken together, these findings suggest that AOPPs cause pain hypersensitivity in rats, and extracellular AOPPs accumulation triggered Nox4-dependent ROS production, which activated JNK, and induced DRG neurons apoptosis by activating caspase 3 and PARP-1.